DEMOLISHING STEREOTYPES IN PAUL BEATTY’S NOVEL THE SELLOUT (2015) - Ridho Yosfika; Desvalini Anwar; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2018)
The purposes of this analysis are to expose the issue about the acts of demolishing stereotypes which is done by African-American man and to know the contribution of the narrator, plot and setting in revealing the acts of demolishing stereotypes. This analysis is related to the concept of orientalismby Edward W. Said that is supported by the text and context based interpretation. The result of this analysis shows the actions of an African-American man who struggles to demolish the negative stereotypesthat can be seen from his efforts to live as an independent person andhave good behavior.